Same-sex love in India : a literary history - Vanita, Ruth; Kidwai, Saleem (Haryana : Penguin India, 2008)
In 2009, the Delhi High Court's historic ruling, which declared Section 377 unconstitutional, referenced Same-Sex Love in India. This was also affirmed by the Supreme Court's 2018 decision upholding that judgment. All the petitions challenging this anti-sodomy law have cited this groundbreaking book to demonstrate that homosexuality is not a foreign concept. Same-Sex Love in India is the book that uncovered the rich, undeniable history of same-sex love and desire in the Indian subcontinent.
Includes index.
Keywords: Homosexuality